2017
DOI: 10.1186/s13256-017-1406-0
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management during adenotonsillectomy for twins with congenital insensitivity to pain with anhidrosis: two case reports

Abstract: BackgroundCongenital insensitivity to pain with anhidrosis is a rare autosomal recessive disorder characterized by hyperpyrexia, anhidrosis, pain insensitivity, self-inflicted injuries, and intellectual disability. The anesthetic management of these patients is challenging owing to the high risk of perioperative complications resulting from their autonomic dysfunction, such as hyperthermia, hypotension, and bradycardia, which result from autonomic nervous system dysfunction.Case presentationTwo 3-year-old Han … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Some studies found that the Bispectral index (BIS) and Narcotrend are useful tools for monitoring the depth of anesthesia in such patients. 15,20 Despite the necessity to warm our patient to prevent hypothermia, the temperature must be closely monitored to detect and manage hyperthermia. There is no evidence of a correlation between CIPA patients and malignant hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found that the Bispectral index (BIS) and Narcotrend are useful tools for monitoring the depth of anesthesia in such patients. 15,20 Despite the necessity to warm our patient to prevent hypothermia, the temperature must be closely monitored to detect and manage hyperthermia. There is no evidence of a correlation between CIPA patients and malignant hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, better perioperative body temperature management is necessary. Some studies found that the Bispectral index (BIS) and Narcotrend are useful tools for monitoring the depth of anesthesia in such patients 15,20 . Despite the necessity to warm our patient to prevent hypothermia, the temperature must be closely monitored to detect and manage hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative bradycardia was also observed in 2.8% of CIPA cases [ 13 ]. In pediatric patients, cardiovascular complications were reported to be common [ 3 ] and to sometimes induce hemodynamic change by an unpleasant sensation [ 3 , 14 ]; therefore, attention should be paid to hemodynamics in patients with CIPA, even if a compensatory response is present.…”
Section: Discussionmentioning
confidence: 99%
“…So that in some cases, patients with this condition do not require opiates during surgery because they already have congenital analgesia. 23…”
Section: Congenital Insensitivity To Pain With Anhidrosis (Cipa)mentioning
confidence: 99%